Hubungan Akses Sanitasi Dasar dengan Kejadian Stunting di Wilayah Kerja UPTD Puskesmas Syekh Ahmad Pue Lasadindi Toaya Kecamatan Sindue Kabupaten Donggala - Wantah, firmansyah; Sanjaya, Kiki; Wijaya, Wahyu; Buchaer, Nur Hikmah; Krisnasari, Sendhy; Wahid, Riri Suwahyuni (Tadulako University, 2024)
ABSTRACT WHO states that stunting is a major public health problem before the age of five if the prevalence is 20% or more. The earlier increase was due to several factors, including cleanliness or environmental health. According to the 2018 Central Sulawesi Riskesdas report, there was an increase in malnutrition in toddlers by 13.8%. The highest rate was found in Donggala district at 23.5%. This study aims to determine the relationship between UPTD Puskesmas Syekh Ahmad Pue Lasadindi Toaya with the emergence of disease development. This type of research is cross sectional quantitative research.Pengumpulan sampel menggunakan cluster sample. The population of this study consisted of 432 children with stunting. The number of samples consisted of 100 respondents. The data obtained was evaluated statistically using the chi-square test. The results showed that there was an increase in factors and there was no relationship where the results found that respondents had clean water (p = 0.066), used a latrine (p = 1,000), had a bed (p = 0.722), and SPAL (p = 0.708). Suggestions from UPTD Puskesmas Syekh Ahmad Pue Lasadindi Toaya health service providers are encouraged to continue to monitor children's growth regularly and educate families about the importance of cleanliness. Keywords : Toddlers, Stunting, Environmental Sanitation.